2005
DOI: 10.1007/bf03033982
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of nicotine against salsolinol-induced cytotoxicity: Implications for parkinson’s disease

Abstract: Parkinson's disease is associated with degeneration of dopaminergic cell bodies in the substantia nigra. It has been suggested that salsolinol, an endogenous metabolite of dopamine, may be involved in this process. An inverse relationship between Parkinson's disease and smoking (nicotine intake) has been observed in epidemiological studies. Moreover, neuroprotective effects of nicotine in various experimental models have been observed. In this study we sought to determine whether salsolinol-induced cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 22 publications
1
36
0
1
Order By: Relevance
“…Copeland et al sought to determine whether salsolinol-induced apoptosis could be prevented by nicotine. They pretreated the neuroblastoma cell line SH-SY5Y with 0.1 mM nicotine and then induced apoptosis with 0.8 mM salsolinol for 24 h. Their study revealed that nicotine pretreatment resulted in inhibition by more than 50% of salsolinol-induced cytotoxicity (p \ 0.01), which was blocked by mecamylamine, a non-selective nicotinic antagonist as well as conotoxins with selective antagonism against a3-containing nAChRs [25].…”
Section: Cells From the Neuronal Systemmentioning
confidence: 97%
“…Copeland et al sought to determine whether salsolinol-induced apoptosis could be prevented by nicotine. They pretreated the neuroblastoma cell line SH-SY5Y with 0.1 mM nicotine and then induced apoptosis with 0.8 mM salsolinol for 24 h. Their study revealed that nicotine pretreatment resulted in inhibition by more than 50% of salsolinol-induced cytotoxicity (p \ 0.01), which was blocked by mecamylamine, a non-selective nicotinic antagonist as well as conotoxins with selective antagonism against a3-containing nAChRs [25].…”
Section: Cells From the Neuronal Systemmentioning
confidence: 97%
“…Cell viability was quantitatively determined using a 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) colorimetric assay as described in detail previously (Copeland et al 2005(Copeland et al , 2007. Briefly, cells (1.5 9 10 4 cells per well) were plated in a 96-well plate in above media.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…The observance of high levels of salsolinol in the cerebrospinal fluid of patients with PD has led to the suggestion that salsolinol might be involved in the etiology or loss of dopamine neurons in at least some Parkinson patients (Storch et al 2002;Maruyama et al 2004). A neuroprotective effect of nicotine against salsolinol-induced toxicity in immortal SH-SY5Y cells was recently reported (Copeland et al 2005(Copeland et al , 2007. SH-SY5Y cells, derived from human neuroblastoma cells are extensively used as a model to study nigral dopaminergic neurons as they express high level of dopaminergic activity (Storch et al 2002;Maruyama et al 2004;Naoi et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Different groups have investigated the effects of nicotine on apoptosis both in vitro and in vivo, and they have revealed a correlation between nicotine exposure and apoptosis. Several studies have reported that nicotine has a protective effect via inhibiting apoptosis [1,2,3,4,5,6,7], while others have shown the opposite [8,9,10,11,12]. Recent studies have shown that nicotine can increase oxidative stress, which may be associated with apoptosis [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%